An Extra Hour: Maternal Outcomes With Longer Expectant Management of Second Stage of Labor [15C]. (May 2016) - Skeith, Ashley; Niu, Brenda; Lee, Vanessa; Tuuli, Methodius; Cahill, Alison G.; Caughey, Aaron B.
Abstract : INTRODUCTION: ACOG recently recommended an increase of one hour in the maximum time spent laboring in the second stage in an effort to prevent primary cesarean deliveries. In nulliparous women with epidural analgesia, this indicated an increase in allowance of second-stage from 3 to 4 hours. This study examined the difference in maternal outcomes in the context of a longer second stage. METHODS: A decision-analytic model was created comparing outcomes associated with delivery at 3 hours in second stage versus expectant management until 4 hours in a theoretical cohort of 272, 000 women. All probabilities and utilities were derived from the literature. Outcomes included mode of delivery, chorioamnionitis, post-partum hemorrhage, severe perineal lacerations and maternal deaths. RESULTS: Expectant management until 4 hours led to 55, 488 fewer cesarean deliveries, 16, 263 fewer cases of post-partum hemorrhage, and 1 fewer maternal deaths than immediate delivery at 3 hours. However, this strategy would lead to 7, 906 more severe perineal lacerations. Ultimately, expectant management to 4 hours was the optimal strategy as it maximized total QALYs. Sensitivity analysis indicated that allowing 4 hours in second stage was optimal until the probability of cesarean delivery at 4 hours decreased to 44.2%, after which delivering at 3 hours was the preferred strategy. CONCLUSION: Expectant management of the second stage of labor until 4 hours is the optimal strategy to prevent primary cesarean deliveries and improve maternal outcomes, with the exception of severe lacerations. As practice evolves, outcomes related to changing practice deserve further research and additional consideration of neonatal outcomes.